Impact of anodic bonding on transmission loss in 23GHz pressure transducers. (September 2019) - De Paolis, M.V.; Philippe, J.; Rumeau, A.; Coustou, A.; Charlot, S.; Aubert, H.; Pons, P.
Abstract: This paper analyses the impact of anodic bonding technique on the transmission loss in 23GHz pressure transducers. The transducers consist of a thin high resistivity silicon membrane and a 23GHz planar resonator placed inside a cavity. Two types of transmission line are used here for designing the resonators: probe-fed coplanar lines and aperture-coupled microstrip ones. Transducers based on aperture-coupled microstrip resonators and manufactured from the anodic bonding process for assembling the silicon membrane to the glass substrate are the most promising low-loss solution. It is actually shown that, at the resonant frequency of the planar resonator, the measured transmission loss in a probe-fed coplanar transducer is about 4 dB when using bonding with the photoresist as an intermediate layer, while it is only of 2.55 dB when applying the anodic bonding assembling process. However, we report for the first time that very high and unexpected transmission loss (>30 dB) occurs when using anodic bonding technique to manufacture the 23GHz aperture-coupled microstrip transducers. Highlights: The impact on pressure transducers' performance of the anodic bonding process used for assembling the high resistivity silicon (HR-Si) wafer to the glass substrate is investigated. The measured results achieved for 23GHz pressure transducers are reported. Two types of transmission lines (the probe-fed coplanar lines and the aperture-coupled microstrip ones) and two bonding techniques (anodic bonding and photoresist one) have been considered. At the resonant frequency, the measured transmission loss in a probe-fed coplanar transducer is about 4dB when using photoresist bonding, while it is only of 2.55dB when applying the anodic bonding assembling process. Very high and unexpected transmission loss (>30dB) was measured for the aperture-coupled sensors assembled from anodic bonding.